2022
DOI: 10.1002/jper.22-0273
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal risk score: Initiation and model validation for 6,762 teeth

Abstract: Background Tooth‐level prognostic systems are valuable tools for treatment planning and risk assessment of periodontally involved teeth. Recently the Miller‒McEntire prognosis index was found to outperform comparable systems. However, it had some limitations. The present study aimed to develop and evaluate the prognostic performance of a modified version that addresses most limitations of the previous model called the periodontal risk score (PRS). Methods Data were retrieved retrospectively from patients who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In terms of risk or prognosis determination, tooth-level prognostic systems provide better information. Saleh et al reported recently that the periodontal risk score (PRS), which includes parameters such as age, smoking, diabetes, tooth type, mobility, probing depth, and furcation involvement, was able to predict long-term tooth loss ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of risk or prognosis determination, tooth-level prognostic systems provide better information. Saleh et al reported recently that the periodontal risk score (PRS), which includes parameters such as age, smoking, diabetes, tooth type, mobility, probing depth, and furcation involvement, was able to predict long-term tooth loss ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…to display excellent predictive capability for nonmolar anterior as well as posterior tooth loss due to periodontitis. [ 11 ] The PRS was retrospectively able to predict tooth loss with a very high accuracy even in a population treated by dental students and periodontics residents. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] The PRS was retrospectively able to predict tooth loss with a very high accuracy even in a population treated by dental students and periodontics residents. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…This introduces the risk of incorporation bias-where the model performance is artificially inflated by including the predictors as part of the outcome definition (Moons et al 2019). This would be less of a concern in studies where the cause of extraction was determined at the time of extraction (Saleh et al 2022). Narrowing the outcome to TLP also necessitates a competing risk framework: not accounting for competing risks may lead to substantial miscalibration and overestimation of risk (Berry et al 2010).…”
Section: Main Findings and Quality Of Evidencementioning
confidence: 99%